Exploring the key success strategy for mobile game developers: A distinguish between premium and freemium versions - Dinata, Hendra; Suryani, Erma; Purnomo, Jerry Dwi Trijoyo (Edelweiss Applied Science and Technology, 2024)
This study aims to investigate the most effective revenue-generating strategies for mobile game developers, particularly in choosing between premium and freemium versions since these two versions come with distinct characteristics. This study employed a qualitative approach, interviewing five gaming studio managers in Indonesia to analyze their experiences and strategies to manage activities at different phases of game development—pre-release and post-release—depending on their chosen monetization strategy. The findings indicate that premium game version developers demonstrate heightened activities during the pre-release phase, dedicating substantial efforts to advertising campaigns, customer engagement, and providing a game demo. In contrast, freemium game version developers exhibit increased activities in the post-release phase, primarily focusing on advertising campaigns, selling virtual items at low prices, giving virtual item rewards, and updating content. In conclusion, the optimal strategy for game developers depends on the version they pursue. Pre-release phases are critical for the success of premium game versions, while freemium versions require an ongoing focus in the post-release phase. These insights offer game developers direction on resource allocation and effort concentration according to their selected monetization strategy, hence facilitating revenue maximization and optimization of the game development process.